2012
DOI: 10.3233/wor-2012-0403-1891
|View full text |Cite
|
Sign up to set email alerts
|

Musculoskeletal Disorders in Caregivers of Children with Cerebral Palsy Following a Multilevel Surgery

Abstract: The patients of cerebral palsy need assistance for their self activities which expose the caregivers to different risk factors of musculoskeletal disorders. But there is a scarcity of studies revealing the prevalence and the risk factors present among the caregivers of the cerebral palsy children. This lead to formulate a study to identify prevalence and risk factors among the caregivers of cerebral palsy children. Result revealed that most of the caregivers among both the groups were female (63.4% and 69.3%).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 13 publications
0
15
0
2
Order By: Relevance
“…[14][15][16][19][20][21] More behavioral and somatic concerns include lack of exercise, poor sleep, fatigue, weight gain or loss leading to impaired immune system function, coronary heart disease, and early mortality. 2,5,22,23 Caregivers of both older children and adult patients also report a signi cantly higher prevalence of musculoskeletal pain, attributed to lifting and transferring heavy loads, 24,25 paralleling load-related problems widely reported by caregivers based in medical settings. 26 From a biopsychosocial perspective, these symptoms are highly interdependent.…”
Section: Caring For Caregiversmentioning
confidence: 88%
“…[14][15][16][19][20][21] More behavioral and somatic concerns include lack of exercise, poor sleep, fatigue, weight gain or loss leading to impaired immune system function, coronary heart disease, and early mortality. 2,5,22,23 Caregivers of both older children and adult patients also report a signi cantly higher prevalence of musculoskeletal pain, attributed to lifting and transferring heavy loads, 24,25 paralleling load-related problems widely reported by caregivers based in medical settings. 26 From a biopsychosocial perspective, these symptoms are highly interdependent.…”
Section: Caring For Caregiversmentioning
confidence: 88%
“…Além disso, a presença de condições patológicas esteve presente em 3 dos 4 cuidadores com idades mais elevadas. No total foram 17 indivíduos, sendo a lombalgia a mais prevalente, corroborando os achados Sharan et al 25 onde ao analisarem dois grupos de cuidadores, sendo o primeiro grupo composto por 257 cuidadores de crianças com PC e o segundo grupo por 117 cuidadores de crianças em atendimento ambulatorial com problemas ortopédicos diversos, verificaram resultados significativos quanto à presença de alterações musculoesqueléticas no cuidador, sendo as dores na região inferior das costas as mais frequentes (p = 0,004), seguidas de dores nos ombros. 12 Contudo, no presente estudo não houve significância estatística (p = 0,36), o que se assemelha ao estudo de Yilmaz, 24 onde ao avaliar a qualidade de vida dos cuidadores através da SF-36, não encontraram significância com a presença de condições patológicas.…”
Section: Discussionunclassified
“…Research shows that caregivers suffer from depression, anxiety and poor physical health (Oyebode, 2003). Studies have revealed that caregivers of various patients are exposed to different risk factors for musculoskeletal disorders (Nelson et al, 2006;Tinubu et al, 2010;Sharan et al, 2012). Although physical exercise has been found to reduce risk of cardiovascular disease, minimize falls and to improve balance, gait, endurance and general quality of life (Dubbert, 2002;Blake et al, 2009) it has been shown that caregivers engage in less physical activity and participate in fewer formal physical activities compared with non-caregivers (Burton et al, 1997;Fredman et al, 2006).…”
Section: Introductionmentioning
confidence: 99%